MOTIVASI KERJA PEGAWAI DALAM PELAKSANAAN TUGAS PADA KANTOR DINAS PENDIDIKAN KABUPATEN PASAMAN BARAT - Reni Padhila (Universitas Negeri Padang, 2013)
This research is motivated because of the phenomena associated with low employee motivation at the office of District Education West Pasaman. The purpose of this study was to obtain information concerning: (1) performance of employees in the performance of duties in the office of West Pasaman education, (2) excitement in the performance of duties of employees working at the Education Department's office of West Pasaman, (3) employee responsibilities in the implementation of duty at the office of District Education West Pasaman, (4) the impact of incentives in the performance of duties in the office of District EducationWestPasaman.The study population was all employees of the Education Department's office of West Pasaman many as 80 people. The number of samples is 68 people using Krjcie table. Means of collecting data in this study is a questionnaire, which is arranged in the form of a Likert scale that has been tested for validity and reliability. Data analysis techniques using the formula Mean (average).The results showed that: (1) performance in the implementation of the tasks are quite high with the acquisition of the category average (3.59), (2) excitement in the performance of duties of employees working at the office of the District Education Office is located on the West Pasaman enough tinggidengan category average gain (3.26), (3) employee responsibilities in the implementation of tasks in a category quite well with the average gain (3.19), selanjtnya (4) the effect of employee incentives in the discharge also showed moderately high with an averagegain(3.27).Thus it can be said that the motivation of employees in the performance of duties in the office of the District Education Office West Pasaman high enough. Key words : Employee Motivation